2021
DOI: 10.1007/s00253-021-11362-3
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of Akkermansia muciniphila with host-derived substances, bacteria and diets

Abstract: Trillions of microbes inhabit the human gut and build extremely complex communities. Gut microbes contribute to host metabolisms for better or worse and are widely studied and associated with health and disease. Akkermansia muciniphila is a gut microbiota member, which uses mucin as both carbon and nitrogen sources. Many studies on A. muciniphila have been conducted since this unique bacterium was first described in 2004. A. muciniphila can play an important role in our health because of its beneficial effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 93 publications
0
31
0
1
Order By: Relevance
“…Finally, we found that metagenome inference indicates that the propionate metabolism was one of the most intriguing gene pathways enriched in our mice with inulin supplementation under a fat-enriched diet. Inulin might contribute to the citric acid cycle through propionate, which is considered a gluconeogenic short-chain fatty acid [36]; however, it is well known that A. muciniphila can degrade mucin, a complex glycoprotein secreted by the gut epithelial cells in mammals [37,38] and generate short-chain fatty acids such as propionate and acetate, which in turn stimulate the epithelial cells to further synthesize and excrete more mucin, or to stimulate the growth of other commensal beneficial butyrateproducing bacteria within the intestine in a complex "cross-feeding" mechanism [39,40] In this context, it has been reported that oral administrations of fructo-oligosaccharides (FOS) such as inulin (a polysaccharide fructan) are able to act as a prebiotic, increasing the A. muciniphila abundance in diet-induced or genetically induced obese mice [41,42]. Human studies indicates that the so-called FODMAP (fermentable oligo-, di-and monosaccharides and polyols) diet may increase the levels of A. muciniphila in healthy subjects or in subjects with Crohn s disease [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that metagenome inference indicates that the propionate metabolism was one of the most intriguing gene pathways enriched in our mice with inulin supplementation under a fat-enriched diet. Inulin might contribute to the citric acid cycle through propionate, which is considered a gluconeogenic short-chain fatty acid [36]; however, it is well known that A. muciniphila can degrade mucin, a complex glycoprotein secreted by the gut epithelial cells in mammals [37,38] and generate short-chain fatty acids such as propionate and acetate, which in turn stimulate the epithelial cells to further synthesize and excrete more mucin, or to stimulate the growth of other commensal beneficial butyrateproducing bacteria within the intestine in a complex "cross-feeding" mechanism [39,40] In this context, it has been reported that oral administrations of fructo-oligosaccharides (FOS) such as inulin (a polysaccharide fructan) are able to act as a prebiotic, increasing the A. muciniphila abundance in diet-induced or genetically induced obese mice [41,42]. Human studies indicates that the so-called FODMAP (fermentable oligo-, di-and monosaccharides and polyols) diet may increase the levels of A. muciniphila in healthy subjects or in subjects with Crohn s disease [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Since A. muciniphila was first described in 2004, many studies have been conducted ( Hagi and Belzer, 2021 ). A number of studies have shown that A. muciniphila is a promising target for the treatment of gut microbiota-related diseases, such as colitis, metabolic syndrome, and immune diseases ( Zhou, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only two species of Akkermansia , A. muciniphila and A. glycaniphila ( Derrien et al., 2004 ; Ouwerkerk et al., 2016 ), have been isolated and comprehensively described. Akkermansia muciniphila is widely present in the intestinal mucosa of human ( Ley et al., 2008 ; Presley et al., 2010 ; Belzer and de Vos, 2012 ; Falony et al., 2016 ), and it can degrade the mucin in epithelial mucosa and produce diverse structural molecules such as short-chain fatty acids ( Derrien et al., 2004 ; Derrien et al., 2010 ; Hagi and Belzer, 2021 ). The host range of the Akkermansia genus is wide, ranging from mammals (mainly A. muciniphila ) to non-mammals (e.g., A. glycaniphila is isolated from python ( Ouwerkerk et al., 2016 )) that differed greatly in physiology, dietary structure, and composition of mucinous proteins in the gut ( Ley et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%